Organic Substrate Selection Criteria For Sulfate Reduction Treatment Of Mining Influenced Waters ? Introduction - P. A. Hagerty (Society for Mining, Metallurgy & Exploration, 2011)
Biological treatment of metals-impacted water using sulfate reduction is a viable means of treatment that has been applied in pilot and full scale at numerous projects. One of the fundamental challenges with this type of treatment is the selection of an appropriate substrate to support the sulfate reduction process long-term. The substrate degradation products provide a carbon source and an electron donor for metabolism by sulfate-reducing bacteria and consequently organic characteristics are critical; however, the physical attributes of the substrate are equally critical to an efficient and optimized substrate mix. This paper explores the affect of particle size (a.k.a. grain size) of several substrate mixes on the treatment efficiency of sulfate reducing treatment systems. Substrate selection can be separated into two phases of evaluation, the primary selection phase and the secondary optimization phase. The primary selection phase considers such fundamental attributes as source availability, economics, bioavailability and longevity. These fundamental activities are conducted in order to identify potential candidate ingredients of the substrate mix which are regionally available, economically viable and consistent with the biogeochemical aspects of the project. Recent work has been conducted in the development of testing protocol for organic substrates to quantify bioavailability (Martinez Hernandez et al. 2010, Place et al. 2006) as part of the primary selection phase. Once the substrate ingredients have been selected based on the primary criteria, the mixture of these ingredients is then developed based on an optimization process, including consideration of the substrate ingredient?s particle size distribution.